2014
DOI: 10.1152/ajpgi.00397.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory signaling by CB1 receptors in smooth muscle mediated by GRK5/β-arrestin activation of ERK1/2 and Src kinase

Abstract: We examined whether CB 1 receptors in smooth muscle conform to the signaling pattern observed with other G i-coupled receptors that stimulate contraction via two G␤␥-dependent pathways (PLC-␤3 and phosphatidylinositol 3-kinase/integrin-linked kinase). Here we show that the anticipated G␤␥-dependent signaling was abrogated. Except for inhibition of adenylyl cyclase via G␣ i, signaling resulted from G␤␥-independent phosphorylation of CB 1 receptors by GRK5, recruitment of ␤-arrestin1/2, and activation of ERK1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…These data are consistent with the recently emerging concept of b-arr-dependent CB 1 R signaling, i.e. a b-arr-mediated ERK1/2 phosphorylation following CB 1 R activation (Ahn et al 2013a, Mahavadi et al 2014.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data are consistent with the recently emerging concept of b-arr-dependent CB 1 R signaling, i.e. a b-arr-mediated ERK1/2 phosphorylation following CB 1 R activation (Ahn et al 2013a, Mahavadi et al 2014.…”
Section: Discussionsupporting
confidence: 91%
“…8A). Recent data have suggested that CB 1 R-induced activation of p42/44 MAPK (ERK1/2), which was formerly suggested to occur via G-protein-dependent pathways (Galve-Roperh et al 2002, Davis et al 2003, Dalton & Howlett 2012, is also mediated by b-arrs (Ahn et al 2013a, Mahavadi et al 2014. Therefore, we aimed to study how the ERK1/2 responses correlate with the G-protein activation and/or b-arr recruitment of the biased CB 1 R mutants.…”
Section: B-arr1 Recruitment Of Cb 1 R-aay Mutant Is Robustly Enhancedmentioning
confidence: 98%
See 1 more Smart Citation
“…The signaling pathway utilized by CB 1 receptors in gastric smooth muscle cells to attenuate acetylcholine (M3 muscarinic)- and Gq-mediated contraction was comprehensively described by Mahavadi and colleagues (Mahavadi, Sriwai, Huang, Grider, & Murthy, 2014). In dispersed or cultured rabbit gastric smooth muscle cells, anandamide stimulation of the CB 1 receptor activated predominantly Gi2, and inhibited cAMP accumulation.…”
Section: Cannabinoid Receptor Signaling Pathways Associated With Diffmentioning
confidence: 99%
“…1A). The COOH-terminal sequence of GRK2 acts as a specific G␤␥ (but not G␣) antagonist by binding to G␤␥ and blocking its interaction with effectors such as GRK2 (14,16,18,38). Treatment of freshly dispersed smooth muscle cells with DPDPE also stimulated cSrc phosphorylation, which was abolished in smooth muscle cells pretreated with the cSrc inhibitor PP2 or the PI 3-kinase inhibitor LY294002 (Fig.…”
Section: Dpdpe-stimulated Phosphorylation Of Csrc Mediated By G␤␥-depmentioning
confidence: 92%